Comprehensive Assessment of Transformer Oil After Thermal Aging: Modeling for Simultaneous Evaluation of Electrical and Chemical Characteristics - Sifeddine Abdi; Noureddine Harid; Besseri Boubaker Achraf; Abderrahmane (Manu) Haddad; Ahmed Boubakeur (Energies)
This paper reports the results of an experimental study that examines the impact of thermal aging on the electrical and chemical properties of insulating oil used in power transformers. Transformer-oil samples were thermally aged over a 5000 h period at different temperatures varying between 80 °C and 140 °C, replicating both normal and extreme operating conditions. Measurements of breakdown voltage, dielectric dissipation factor, acidity, and water content were taken at 500 h intervals. A novel approach of this research is the integration of these electrical and chemical characteristics into a comprehensive exponential regression analysis model. The results indicate that breakdown voltage and resistivity decrease with aging time, whereas the dielectric dissipation factor, acidity, and water content increase with aging time. The degradation trends computed by the proposed model show close correlation with both electrical and chemical properties, with correlation coefficients generally equal to or exceeding 90%, which demonstrates its reliability in predicting aging behavior of transformer oil. This integrated approach offers valuable insights into the combined electrical and chemical degradation processes due to thermal aging and assists in the condition assessment of power transformers.